Progress of dendritic cell-based cancer vaccines for patients with hematological malignancies - Ni, Ming; Hoffmann, Jean-Marc; Schmitt, Michael; Schmitt, Anita (Expert opinion on biological therapy, 2016)
Introduction: Dendritic cells (DCs) are the most professional antigen-presenting cells eliciting cellular and humoral immune responses against cancer cells by expressing these antigens on MHC class I/II complexes to T cells. Therefore, they have been employed in many clinical trials as cancer vaccines for patients with cancer. This review focuses on the use of DCs in leukemia patients expressing leukemia-associated antigens (LAAs).Areas covered: The contribution of both stimulating vs. tolerogenic DCs as well as of other factors to the milieu of anti-leukemia immune responses are discussed. Several DC vaccination strategies like leukemia lysate, proteins and peptides have been developed. Next generation DC vaccines comprise transduction of DCs with retroviral vectors encoding for LAAs, cytokines and costimulatory molecules as well as transfection of DCs with naked RNA encoding for LAAs. Published as well as ongoing clinical trials are reported and critically reviewed.Expert opinion: Future results will demonstrate whether next-generation DCs are really superior to conventional pulsing with peptide, protein or tumor lysate. However, currently available methods based on nucleic acid transfection/transduction are tempting in terms of material production costs and time for clinical application according to good manufacturing practice (GMP).